Time course of Graves’ orbitopathy after total thyroidectomy and radioiodine therapy for thyroid cancer - Louvet, Camille (Medicine (Baltimore), 2016)
The risk of cancer is relatively higher in Graves’ patients presenting simultaneously with thyroid nodules. Radioiodine (RAI) therapy recommended in high-risk differentiated thyroid carcinoma may be associated with worsening of a pre-existing Graves’ orbitopathy (GO) or developing a new onset. The impact of RAI therapy in patients with differentiated thyroid cancer on the course of a pre-exisiting GO has not been specifically investigated. The aim of this study is to assess the influence of RAI treatment administered for differentiated thyroid cancer on the course of a pre-existing GO. This is a retrospective multicenter study including 35 patients from the University Hospital of Clermont-Ferrand (7 patients) and Lyon-Est (6 patients) in France and from a literature review published as case reports or studies (22 patients). Seven patients exhibited a worsened pre-existing GO after total thyroidectomy followed by RAI treatment for thyroid cancer. Older men, those who initially presented with a lower clinical score of GO before RAI therapy, received higher doses of (131)I especially when prepared with recombinant thyroid-stimulating hormone, and/or not prepared with glucocorticoids during RAI are at a higher risk to worsen their GO. This study is the first and complete study collection. We describe worsening of GO in 20% of patients after RAI treatment for thyroid cancer and determine a pool of predictive factors.